Natural polymer-based scaffolds for soft tissue repair - Chen, Meiwen; Jiang, Rui; Deng, Niping; Zhao, Xiumin; Li, Xiangjuan; Guo, Chengchen (Frontiers in Bioengineering and Biotechnology, 2022)
Soft tissues such as skin, muscle, and tendon are easily damaged due to injury from physical activity and pathological lesions. For soft tissue repair and regeneration, biomaterials are often used to build scaffolds with appropriate structures and tailored functionalities that can support cell growth and new tissue formation. Among all types of scaffolds, natural polymer-based scaffolds attract much attention due to their excellent biocompatibility and tunable mechanical properties. In this comprehensive mini-review, we summarize recent progress on natural polymer-based scaffolds for soft tissue repair, focusing on clinical translations and materials design. Furthermore, the limitations and challenges, such as unsatisfied mechanical properties and unfavorable biological responses, are discussed to advance the development of novel scaffolds for soft tissue repair and regeneration toward clinical translation.